Why subsistence matters. Issue 4 (April 2019) - Ready, Elspeth
Abstract : Subsistence, including hunting, sharing the proceeds of the hunt, and the social relations associated with these activities, is central to Inuit life. Here I synthesise my previous research on food security, economics, hunting and sharing in Kangiqsujuaq, Nunavik, tracing some of the pathways that connect traditional harvesting and sharing with political, economic and social life in the settlement today. The results reveal that some of the most fundamental aspects of life in the settlement – not just food access but also local leadership and the formation of family units – continue to be closely associated with the hunting and sharing of traditional foods. At the same time, broader economic forces threaten the ability of many Inuit to fully participate in subsistence activities. Understanding the social importance of traditional harvesting and sharing, and its relationship to the economic strategies of households, therefore remains necessary to approaching economic and social problems in northern communities. Because of the patterns of socioeconomic differentiation observed in Kangiqsujuaq and other settlements, the dynamics of complex social systems, including poverty traps, and the responses of norms and values to changed socioeconomic structures emerge as critical areas for future research.